Analisis Pertumbuhan Ekonomi, Ketimpangan Daerah dan Tingkat Kemiskinan antar Provinsi di Pulau Kalimantan - Yati, Mariata; Hasudungan, Febriant; Londong, Esau; Panca Kurniasih , Erni (Prodi Manajemen, Fakultas Ekonomi, Universitas Pamulang, 2024)
The economic growth of a region is reflected in GDP and GRDP. It is important to achieve economic growth and economic equality so that prosperity increases evenly. Economic inequality can cause social problems and risk regional disintegration. Even though high economic growth can occur, it does not always mean that people's welfare increases automatically, especially for the poor. Differences in development and infrastructure between regions also affect people's income. This research aims to examine the economic situation, regional inequality and poverty levels in Kalimantan Province. It is hoped that the results of this research will provide useful information for local governments in future policy making. This research is descriptive in nature and uses a qualitative approach to understand social phenomena through secondary data from the Central Statistics Agency (BPS) and related regional institutions. Economic growth in Kalimantan province experienced fluctuations during the 2014-2023 period. Although there are annual variations, in general there is an upward trend after 2020. The Williamson Index in Kalimantan province experienced small variations from year to year during the 2014-2023 period. The poverty level in Kalimantan province tends to vary from year to year during the 2014-2023 period.